2023
DOI: 10.1002/aps3.11527
|View full text |Cite|
|
Sign up to set email alerts
|

A comparison of freezer‐stored DNA and herbarium tissue samples for chloroplast assembly and genome skimming

Abstract: Premise: The use of DNA from herbarium specimens is an increasingly important source for evolutionary studies in plant biology, particularly in cases where species are rare or difficult to obtain. Here we compare the utility of DNA from herbarium tissues to their freezer-stored DNA counterparts via the Hawaiian Plant DNA Library. Methods: Plants collected for the Hawaiian Plant DNA Library were simultaneously accessioned as herbarium specimens at the time of collection, from 1994-2019. Paired samples were sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…While DNA can be stable in dried plant specimens for centuries (Palmer et al, 2011), multiple studies have shown that DNA from herbarium samples tends to become fragmented over time (Särkinen et al, 2012; Krinitsina et al, 2015; Weiß et al, 2016; Shepherd, 2017; Jordon‐Thaden et al, 2020; McAssey et al, 2023). We therefore used universal plant primers with different predicted amplicon sizes to assess DNA quality based on PCR amplification success.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…While DNA can be stable in dried plant specimens for centuries (Palmer et al, 2011), multiple studies have shown that DNA from herbarium samples tends to become fragmented over time (Särkinen et al, 2012; Krinitsina et al, 2015; Weiß et al, 2016; Shepherd, 2017; Jordon‐Thaden et al, 2020; McAssey et al, 2023). We therefore used universal plant primers with different predicted amplicon sizes to assess DNA quality based on PCR amplification success.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Recently, researchers have moved toward storing frozen DNA samples along with typical herbarium samples. McAssey et al ( 2023 ) creatively use a data set—the Hawaiian Plant DNA Library, collected from 1994–2019—with both frozen DNA accessions and herbarium sheets to compare each storage method for use in downstream sequencing applications. A comparison of paired samples revealed that DNA obtained from herbarium specimens was significantly more fragmented than DNA stored in a freezer, and consequently produced lower‐quality chloroplast assemblies.…”
Section: Effect Of Different Storage Methods On Dna Extractionmentioning
confidence: 99%
“…An important aspect is also the studies of phylogenetic relationships. Increasingly, phylogenetic analyses are based on samples collected from herbarium materials, e.g., [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], despite problems related to post-mortem DNA damage [ 23 , 24 ]. Herbaria also play an important role in research related to the distribution of plants.…”
Section: Introductionmentioning
confidence: 99%